Assessment of paediatric Hashimoto's thyroiditis using superb microvascular imaging. Issue 12 (December 2018) - Bayramoglu, Z.; Kandemirli, S.G.; Caliskan, E.; Yilmaz, R.; Kardelen, A.D.; Poyrazoglu, S.; Bas, F.; Adaletli, I.; Darendeliler, F.
Abstract : Aim: To evaluate the role of superb microvascular imaging along with greyscale and Doppler imaging for thyroid gland evaluation in Hashimoto's thyroiditis (HT) versus control subjects. Materials and methods: The study included 33 healthy volunteers with normal ultrasound and laboratory findings and 70 patients with HT based on laboratory and sonographic findings who were undergoing follow-up and receiving medical treatment. HT patients were classified based on the modification of the scheme proposed by Sostre and Reyes that incorporates the extent of hypoechoic foci or patchy infiltration as grade A (foci involving <50% of the gland) and B (foci involving >50% of the gland). Thyroid volume, mean resistive indices, peak-systolic and end-diastolic velocities based on Doppler imaging, and vascularity index via superb microvascular imaging were obtained using a Canon Aplio 500 ultrasound device using a linear 10–14 MHz transducer. Results: Patients with HT had significantly higher median thyroid volume and peak-systolic velocities (7.32 ml and 19 cm/s, respectively) compared to control subjects (4.62 ml and 16 cm/s, respectively). HT patients had significantly higher median vascularity index (VI; 13.5%) compared to control subjects (7.95%). A significant fair positive correlation with VI and anti-thyroglobulin antibody levels ( r =0.356, p< 0.05) and significant moderate positive correlation with VI and anti-thyroid peroxidase antibody levels ( r =0.503, p< 0.05) were found. In HT diagnosis, the optimal VI cut-off value was 10.58% with a sensitivity and specificity of 67.1% and 90%, respectively. Conclusion: Superb microvascular imaging appears to allow assessment of subtle vascularity changes in early HT stages that cannot be detected by Doppler parameters. This technique demonstrates excellent visualization of the microvascular structures and quantitative assessment based on a novel parameter such as VI. Highlights: Hashimoto thyroiditis is the most common thyroiditis affecting the paediatric population. Doppler ultrasound is a commonly utilized modality in evaluation of thyroiditis along with grayscale ultrasonography. Superb microvascular imaging is superior to Doppler ultrasonography in differentiating Hashimoto thyroiditis with subtle gray scale ultrasound findings.